Involvement of Acetylcholine Receptors in Cholinergic Pathway-Mediated Protection Against Autoimmune Diabetes - Fernández-Cabezudo, Maria J.; George, Junu A.; Bashir, Ghada; Mohamed, Yassir A.; Al-Mansori, Alreem; Qureshi, Mohammed M.; Lorke, Dietrich E.; Petroianu, Georg; al-Ramadi, Basel K. (Frontiers in Immunology, 2019)
Type I diabetes (T1D) is a T cell-driven autoimmune disease that results in the killing of pancreatic -cells and, consequently, loss of insulin production. Using the multiple low-dose streptozotocin (MLD-STZ) model of experimental autoimmune diabetes, we previously reported that pretreatment with a specific acetylcholinesterase inhibitor (AChEI), paraoxon, prevented the development of hyperglycemia in C57BL/6 mice. This correlated with an inhibition of T cell infiltration into the pancreatic islets and a reduction in proinflammatory cytokines. The cholinergic anti-inflammatory pathway utilizes nicotinic and muscarinic acetylcholine receptors (nAChRs and mAChRs, respectively) expressed on a variety of cell types. In this study, we carried out a comparative analysis of the effect of specific antagonists of nAChRs or mAChRs on the development of autoimmune diabetes. Co-administration of mecamylamine, a non-selective antagonist of nAChRs maintained the protective effect of AChEI on the development of hyperglycemia. In contrast, co-administration of atropine, a non-selective antagonist of mAChRs, mitigated AChEI-mediated protection. Mice pretreated with mecamylamine had an improved response in glucose tolerance test than mice pretreated with atropine. These differential effects of nAChR and mAChR antagonists correlated with the extent of islet cell infiltration and with the structure and functionality of the -cells. Taken together, our data suggest that mAChRs are essential for the protective effect of cholinergic stimulation in autoimmune diabetes.